A new species and subspecies of genus Chlaenius Bonelli, 1810 with remark on the taxonomic position of Haplochlaenius Lutshnik, 1933 and Vachinius Casale, 1984 and a new synonym of subgenus Macrochlaenites Kuntzen, 1919 (Coleoptera: Carabidae: Chlaeniini). (2nd October 2019) - Azadbakhsh, Saeed; Kirschenhofer, Erich
ABSTRACT: A new species and subspecies of genus Chlaenius Bonelli, 1810 from South East Asia, Indonesia, belonging to the subgenus Haplochlaenius namely Chlaenius ( Haplochlaenius ) ramezani sp. nov ., and Chlaenius ( Haplochlaenius ) pantarensis moradianae ssp. nov ., are described. The new taxa are compared with the related ones. The genus Vachinius and its subgenus Sphodromimus are considered as subgenera of the genus Chlaenius Bonelli, 1810. New combinations for the members of subgenera Vachinius and Sphodromimus are proposed: Chlaenius ( Vachinius ) arakanensis comb. n ., C . ( V .) pseudoglaber comb. n ., C . ( V .) subglaber comb. n ., C . ( Sphodromimus ) burmanensis comb. n ., C . ( S .) deuvei comb. n ., C . ( S .) hajeki comb. n ., C . ( S .) holzschuhi comb. n ., C . ( S .) hunanus comb, n ., C . ( S .) laosensis comb. n ., C . ( S .) luzoensis comb. n ., C . ( S .) pilosus comb. n ., C . ( S .) tamdaoensis comb. n ., C . ( S .) thailandensis comb. n ., C . ( S .) wrasei comb. n . The species C . ( Haplochlaenius ) klapperichi and C . ( Haplochlaenius ) baehri comb. n ., are transferred to Haplochlaenius from Sphodromimus . C . ( S .) flavofemoratus C. (S.) flavofemoratus enleensis and C . ( S .) peterseni New subgenus assignment, are transferred to Sphodromimus from Haplochlaenius . C . ( S .) birmanicus syn. n ., is transferred to Sphodromimus from Haplochlaenius and considered as synonym of Chlaenius ( S .) flavofemoratus . The species Chlaenius (incertae sedis) drescheri and Chlaenius ( Chlaeniellus ) manus New subgenus assignment, are removed from Haplochlaenius . The species Chlaenius ( Macrochlaenites ) akanensis syn. n ., is considered as a synonym of Chlaenius ( Amblygenius ) anthraceus . Checklists of the species of subgenera Haplochlaenius, Vachinius and Sphodromimus are presented. urn:lsid:zoobank.org:pub:58BB5128-5432-47BB-AC63-0F5CB9DD61FB